The cone loading test to estimate deformability moduli of a tropical soil - Salles, Jude Christian; García, Gian Franco Napa; Giacheti, Heraldo Luiz [UNESP] (My University, 2013)
The Cone Loading Test (CLT) consists of the execution of a load test on the piezocone probe in conjunction with the CPT test. The CLT yields the modulus ECLT, a parameter that can be used in the estimative of foundation settlement. It is also presented here the interpretation and the process to determine ECLT values from the stress-displacement curves obtained from cone loading tests. Several CLT tests were conducted at the experimental research site of São Paulo State University, Bauru-SP-Brazil. The geotechnical profile at the studied site is a brown to bright red slightly clayey fine sand, a tropical soil common to this region which is lateritic, unsaturated and collapsible. The results of CLT tests satisfactorily represent the behavior of the investigated soil. The penetrometric modulus ECLT for each depth was calculated considering the elastic behavior in the initial linear segment of the soil stress-strain curve. The ECLT moduli obtained for the various tests were compared to moduli obtained from PMT and DMT test results performed at same studied site. The shear modulus degradation curves obtained from the CLT tests are also presented. The comparison to PMT and DMT results indicates the CLT test is a viable complementary test to the CPT in the quest for better understanding stress-strain behavior of soils. Further, the CLT test provides a graphic visualization of the degradation of the shear modulus with increasing levels of strain. As a hybrid geotechnical test, CPT+CLT can be valuable in the investigation of non-conventional collapsible soils, whose literature lack reference parameters for the prediction of settlement in the design of foundations.
Keywords: Site Characterization; Field test; CPT; Cone loading test; Deformability moduli; Tropical soils